The Dynamic Impact of Financial Globalization, Environmental Innovations and Energy Productivity on Renewable Energy Consumption: Evidence From Advanced Panel Techniques - Majeed, Abdul; Ahmad, Mahmood; Rasheed, Muhammad Faisal; Khan, Muhammad Kaleem; Popp, József; Oláh, Judit (Frontiers in Environmental Science, 2022)
Attaining cleaner production is a major challenge for BRICS economies. In this context, this study explores the effect of financial globalization on renewable energy consumption in BRICS economies from 1990 to 2018. It is probably the first research to study the linkage between financial globalization and renewable energy consumption. Therefore, this research adds to the current literature by presenting new empiric evidence on how financial globalization, in conjunction with environmental innovations, energy productivity, energy prices, and economic growth, affect renewable energy consumption in BRICS economies. In doing so, this research utilized novel econometric methods such as continuously updated fully modified (CUP-FM) and continuously updated bias-corrected (CUP-BC) techniques to evaluate the long-run results. The empirical findings show that financial globalization, environmental innovation, energy productivity, and energy prices promote renewable energy consumption. In contrast, economic growth impedes renewable energy consumption. This study suggests that governments and policymakers in BRICS countries should consider financial globalization and the increasing role of environmental innovations to increase the renewable energy share, which can be the appropriate solutions to the environmental challenges and achieve the Paris Climate Agreement’s goals. BRICS economies require speeding up permits for renewable energy projects, raising tax credits, including substantially more grants and loans, extending timelines for pandemic-affected projects, and investing directly in emerging clean energy sources.